Climate change attribution of Typhoon Haiyan with the Imperial College Storm Model - Nathan Sparks; Ralf Toumi (Atmospheric Science Letters)
Abstract It is difficult to model changes in the likelihood of tropical cyclones under climate change to date. We do this, for the first time, by a applying a stochastic tropical cyclone event set generated by the Imperial College Storm Model to attribute the contribution of climate change to the case of Typhoon Haiyan in 2013. Compared to a pre‐industrial baseline, we estimate that a typhoon with a landfall maximum wind speed like Haiyan was larger by +3.5 m/s. This is in good agreement with previous full physics numerical model estimates. A Haiyan type of event has a current return period of 850 years, and the fractional attributable risk due to climate change is 98%. Without climate change, this event was very unlikely. The type of information available from the IRIS model could inform subsidizing of catastrophe bond yield in the context of the loss and damage fund.